Circulating cardio-enriched microRNAs are associated with long-term prognosis following myocardial infarction - Gidlöf, Olof (BioMed Central, 2013)
BACKGROUND: Increased levels of cardio-enriched microRNAs (miRNAs) have been described in patients with myocardial infarction (MI). We wanted to evaluate the diagnostic and prognostic potential of cardio-enriched miRNAs in patients presenting with a suspected acute coronary syndrome (ACS). METHODS: Cardio-enriched miRNAs (miR-1, miR-208b and miR-499-5p) were measured using real time PCR in plasma samples from 424 patients with suspected ACS treated in a coronary care unit. miRNAs were assessed for discrimination of a clinical diagnosis of myocardial infarction and for association with 30-day mortality and diagnosis of heart failure. Correlation with left ventricular systolic dysfunction as measured by the ejection fraction (LVEF) was also assessed. To confirm myocardial origin miRNA was measured during coronary artery bypass surgery. RESULTS: miRNAs were higher in MI patients and correlated with LVEF (p < 0.001). Discrimination of MI was accurate for miR-208b (AUC = 0.82) and miR-499-5p (AUC = 0.79) but considerable lower than for Troponin T (AUC = 0.95). Increased miRNA levels were strongly associated with increased risk of mortality or heart failure within 30 days for miR-208b (OR 1.79, 95% CI = 1.38-2.23, p = 1 × 10(-5)) and miR-499-5p (OR 1.70, 95% CI = 1.31-2.20, p = 5 × 10(-5)) but the association was lost when adjusting for Troponin T. During surgery miR-208b and miR-499-5p was released in the coronary sinus after cardioplegia-reperfusion to markedly higher levels than in a peripheral vein. CONCLUSIONS: Our findings confirm increased levels of cardio-enriched miRNAs in the blood of MI patients and establish association of increased miRNA levels with reduced systolic function after MI and risk of death or heart failure.